Pharmacist involvement in primary care improves hypertensive patient clinical outcomes - Sookaneknun P. (2014)
BACKGROUND: The practice of pharmaceutical care in primary care settings in Thailand is currently not generally accepted. OBJECTIVE: To evaluate the effect of pharmacist involvement in treatment with hypertensive patients in primary care settings. METHODS: The treatment objective was to stabilize the blood pressure (BP) of hypertensive patients in accordance with the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure guidelines. Patients were randomly assigned to a pharmacist-involved group (treatment) or a group with no pharmacist involvement (control). Pre- and post-test BPs, tablet counts, lifestyle modifications, and pharmacists' recommendations were recorded. The 6-month study was carried out in Mahasarakham University pharmacy and 2 primary care units. Patients were monitored monthly by reviewing their medications and supported by providing pharmaceutical care and counseling. RESULTS: From a total of 235 patients, the treatment group (n = 118) had a significant reduction in both systolic (S) and diastolic (D) BP compared with the 117 patients of the control group (p = 0.037, 0.027, respectively). The 158 patients (76 treatment, 82 control) with BPs ≥140/90 mm Hg at the beginning of the study showed significant BP reductions (p = 0.002 SBP, 0.008 DBP). The proportion of 158 patients whose BP became stabilized was higher in the treatment group (p = 0.017). The treatment group showed significantly better adherence (p = 0.014) and exercise control (p = 0.012) at the end of the study. Physicians accepted 42.72% of medication modifications and 5.34% of the suggestions for additional investigations. CONCLUSIONS: Hypertensive patients who received pharmacist input achieved a significantly greater benefit in BP reduction, BP control, and improvement in adherence rate and lifestyle modification.